(untitled) (International journal of artificial intelligence, 2026)
The article examines the linguistic analysis of the "superfluous man" type in 19th-century Russian literature and its transformation within modern artistic discourse. The author considers this phenomenon not only as a socio-psychological phenomenon but also as a special linguistic model of the individual, manifesting through a stable system of lexical-semantic and syntactic markers.